Whole-Genome Comparisons Among the Genus Shewanella Reveal the Enrichment of Genes Encoding Ankyrin-Repeats Containing Proteins in Sponge-Associated Bacteria - Alex, Anoop; Antunes, Agostinho (Frontiers in Microbiology, 2019)
The bacterial members of the genus Shewanella are widely distributed and inhabit both freshwater and marine environments. Some members of Shewanella have gained considerable attention due to its ability to survive in redox-stratified environments. However, a gap of knowledge exists on the key genomic features of the sponge-associated Shewanella sp. involving the successful host-bacteria interaction, as sponge-symbiotic Shewanella are largely underrepresented in the public repositories. With the aim of identifying the genomic signatures of sponge-Shewanella association, we generated a high-quality genome data of a sponge-associated, Shewanella sp. OPT22, isolated from the intertidal marine sponge Ophlitaspongia papilla and performed comprehensive comparative analyses of 68 genome strains of the genus Shewanella including two previously reported genomes of sponge-associated bacteria, Shewanella spongiae KCTC 22492 and Shewanella sp. Alg231_23. The 16S rRNA-based phylogenetic reconstruction showed the well-supported affiliation of OPT22 and KCTC 22492 with previously reported sponge-associated bacteria, affirming the ‘sponge-specific’ nature of these two bacterial strains isolated from different marine sponge species from the Atlantic and Pacific (East Sea) Oceans, respectively. The genome comparison of the 68 strains of Shewanella inhabiting different habitats revealed the unusual/previously unreported abundance of genes encoding for ankyrin-repeat containing proteins (ANKs) in the genomes of the two sponge-associated strains, OPT22 (ANKs; n=45) and KCTC 22492 (ANKs; n=52), which might be involved in sponge-Shewanella interactions. Focused analyses detected the syntenic organization of the gene cluster encoding major secretion system (type III/IV/VI) components and the presence of effector homologues in OPT22 and KCTC 22492 that seem to play a role in the virulence of the sponge bacteria. The genomic island (GI) of Shewanella sp. OPT22 was identified to localize a gene cluster encoding T4SS components and ANK (n=1), whereas S. spongiae KCTC 22492 harbored a total of seven ANKs within multiple GIs. GIs may play a pivotal role in the dissemination of symbioses-related genes (ANKs) through the horizontal gene transfer, contributing to the diversification and adaptation of sponge-associated Shewanella. Overall, the genome analyses of Shewanella isolates from marine sponges revealed genomic repertoires that might be involved in establishing successful symbiotic relationships with the sponge hosts.